North Korean nuclear operationality : regional security & nonproliferation - Moore, Gregory J. (Baltimore : John Hopkins University Press, 2014)
'Leading Asian and security studies experts consider the question: What would happen if North Korea'goes nuclear?' and their answers are critical. Scholars and policymakers alike need to understand the implications not only for northeast Asian regional security, but also for the international nuclear non-proliferation regime. Moore's contributors evaluate political, economic, and security issues including: how South Korea, China, Japan, and Russia would react to such an event, and the possibility of a regional arms race; what diplomatic and strategic options the U.S. has; and how the global community's expectations regarding nuclear non-proliferation would be effected. Given the instability and mystery surrounding North Korean politics, scholarship on the implications of the country's nuclear capability is critical, which makes this volume with its unique focus a timely addition to the East Asian security studies field'--
Includes bibliographical references : (pages 253-295) and index.
Keywords: Nuclear disarmament -- Korea (North).; Nuclear nonproliferation -- Korea (North).; Nuclear nonproliferation -- East Asia; Security, International -- East Asia